Upgrading polyethylene plastic waste into a biodegradable polymer: Harnessing a hybrid chemical oxidation-biological conversion approach - Firmansyah, Siti Nurjanah; Sun, Habin; Chun-Jae Yoo; Ko, Ja Kyong (Elsevier BV, 2025)
Plastic has garnered significant attention due to the urgent need for effective recycling methods to address its environmental impacts. However, upcycling methods for polyethylene (PE), the most prevalent plastic in use today, have not advanced significantly because its inert structure requires harsh chemical processing conditions. In this study, we present a mild chemical oxidation process using CeO2 as the catalyst to convert polyethylene waste into oxygenates, which are suitable substrates for biological conversion. This process utilizes a heterogeneous catalyst that enhances the separation of reaction products and reduces the risk of metal contamination in subsequent biological processes. Importantly, this method uses an eco-friendly oxidant (O2) and solvent (water), aligning with sustainable practices. Chemically oxidized raw polyethylene derivatives were used as the sole carbon source for the growth of Cupriavidus necator H16, facilitating the biological upgrading of these derivatives into the biodegradable polymer, poly(3-hydroxybutyrate) (PHB). This hybrid process achieved overall PHB yields of 0.22 g PHB/g PE for polyethylene powder, 0.21 g/g for low-density polyethylene bags, and 0.28 g/g for high-density polyethylene bottles. To the best of our knowledge, this study reports the highest PHB production achieved among previously studied hybrid processes that combine chemical oxidation and biological conversion of polyethylene. This integrated approach offers a promising strategy for producing biodegradable materials and advancing the closed-loop upcycling of plastic waste.